2018
DOI: 10.3390/su10062032
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Industrial Discharge Quota (IDQ): A Model Reflecting Opportunity Cost of Performing Ecological Responsibility

Abstract: Abstract:The upper reaches of a river system are often trapped in the dilemma of choosing between industrial development and headwater protection. One of the solutions is eco-compensation, which, however, is a public-fiscal arrangement lacking inspiration and sustainability. Instead, industrial discharge quota (IDQ) was put forward as a marketized approach: the maximum industrial discharge a river can afford is allocated as quotas and quotas are allowed to be traded. However, what pricing principle in the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…A method of ecological compensation for the basin was then proposed according to the opportunity cost [6]. Opportunity cost can be defined as the loss of potential gain from other ecological compensation schemes when one scheme is chosen [7]. Wunder et al suggested that ecological services should be fully market-oriented, including ecological destruction of the basin and the ecological reconstruction and construction compensation of the basin, which would achieve optimal ecological compensation [8].…”
mentioning
confidence: 99%
“…A method of ecological compensation for the basin was then proposed according to the opportunity cost [6]. Opportunity cost can be defined as the loss of potential gain from other ecological compensation schemes when one scheme is chosen [7]. Wunder et al suggested that ecological services should be fully market-oriented, including ecological destruction of the basin and the ecological reconstruction and construction compensation of the basin, which would achieve optimal ecological compensation [8].…”
mentioning
confidence: 99%